2021
DOI: 10.1093/tas/txab055
|View full text |Cite
|
Sign up to set email alerts
|

Determination of in vitro dry matter, protein, and fiber digestibility and fermentability of novel corn coproducts for swine and ruminants

Abstract: New processes are being used in some dry-grind ethanol plants in the United States and Brazil to improve ethanol yield and efficiency of production while also providing nutritionally enhanced corn co-products compared with conventional corn distillers dried grains with solubles (DDGS). The objectives of this study were to determine the chemical composition and in vitro digestibility of 5 conventional corn DDGS sources and 10 emerging novel corn co-products for swine and ruminants, and compare co-products produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
1
0
3
Order By: Relevance
“…In the current study, the CP content in the ethanol industry co-product under study was equivalent to 44.4% and 40.4% on a dry matter and as-fed basis, respectively (Table 2). Other studies involving corn HP-DDG manufactured in Brazil reported similar protein values on a dry matter basis ranging from 46.5% to 45.1% CP (Palowski et al, 2021;Paula et al, 2021;Dias et al, 2023). Overall, our results suggest lower values for certain amino acids in corn HP-DDG compared to National Research Council (2012) on an as-fed basis, specifically, methionine (0.74% vs. 0.80%), threonine (1.61% vs. 1.90%), tryptophan (0.23% vs. 0.38%), and valine (2.15% vs. 2.19%).…”
Section: Resultsmentioning
confidence: 68%
“…In the current study, the CP content in the ethanol industry co-product under study was equivalent to 44.4% and 40.4% on a dry matter and as-fed basis, respectively (Table 2). Other studies involving corn HP-DDG manufactured in Brazil reported similar protein values on a dry matter basis ranging from 46.5% to 45.1% CP (Palowski et al, 2021;Paula et al, 2021;Dias et al, 2023). Overall, our results suggest lower values for certain amino acids in corn HP-DDG compared to National Research Council (2012) on an as-fed basis, specifically, methionine (0.74% vs. 0.80%), threonine (1.61% vs. 1.90%), tryptophan (0.23% vs. 0.38%), and valine (2.15% vs. 2.19%).…”
Section: Resultsmentioning
confidence: 68%
“…Tradicionalmente os produtos resultantes do processo de extração do etanol de milho são os DDG (grãos destilados secos), DDGS (grãos destilados secos + solúveis), WDG (grãos destilados úmidos) e WDGS (grãos destilados úmidos + solúveis), além do CDS (solúveis condensados ou xarope), os quais têm sido extensivamente estudados e utilizados em dietas para bovinos terminados em confinamento nos EUA (KLOPFENSTEIN et al, 2008;NASEM, 2016). Atualmente, com mudanças no processo industrial para maior eficiência na produção de etanol, estão surgindo diferentes produtos no mercado além dos tradicionais, como a fibra seca de milho com solúveis de destilaria (dry bran/fiber plus solubles -DFS), a fibra úmida de milho com solúveis (wet bran/fiber plus solubles -WFS) e grãos destilado de alta proteína (high protein distillers grains -HPDG) (GARLAND, 2018;PALOWSKI et al, 2021).…”
Section: Abstract Inclusion Levels Of Dry Corn Fiber With Distiller's...unclassified
“…As fontes de volumosos são usadas principalmente em dietas de terminação para a manutenção da saúde ruminal (OWENS et al, 1998, NAGARAJA e LECHTENBERG, 2007 e também para que possa ocorrer um estímulo ao consumo de matéria seca (GALYEAN e DEFOOR, 2003) e consumo de energia (ARELOVICH et al, 2008).…”
Section: Referênciaunclassified
“…Esse procedimento consiste em separar a parte fibrosa do grão de milho, previamente moído e cozido, antes da etapa de fermentação do amido. A fibra extraída nesse processo é combinada com os solúveis condensados, extraídos durante a centrifugação da vinhaça, que é obtida após a destilação (Palowski et al, 2021). Isso resulta na produção de um coproduto denominado Farelo ou Fibra úmida de destilaria com solúveis (Wet Distillers Bran plus Solubles -WDBS).…”
Section: Introductionunclassified